Estimating efficiency of survey and commercial trawl gears from comparisons of catch-ratios. (23rd January 2017) - Walker, Nicola D.; Maxwell, David L.; Le Quesne, Will J. F.; Jennings, Simon
Abstract: Assumptions about gear efficiency and catchability influence estimates of abundance, mortality, reference points and catch potential. Despite the need to better quantify fishing effects on some target species and on many non-target species taken as bycatch, there are few gear efficiency estimates for some of the most widely deployed towed fishing gears in the northeast Atlantic. Here, we develop a method that applies generalised additive models to catch-at-length data from trawl surveys and a commercial catch and discard monitoring program in the North Sea to estimate catch-ratios. We then rescale these catch-ratios and fit relationships to estimate gear efficiency. When catches of individuals by species were too low to enable species-specific estimates, gear efficiency was estimated for species-groups. Gear efficiency (and associated uncertainty) at length was ultimately estimated for 75 species, seven species-groups and for up to six types of trawl gear per species or species-group. Results are illustrated for dab ( Limanda limanda), grey gurnard ( Eutrigula gurnardus ) and thornback ray ( Raja clavata ), two common non-target species and a depleted elasmobranch. All estimates of gear efficiency and uncertainty, by length, species, species-group and gear, are made available in a supplementary data file.